A standard set of person‐centred outcomes for diabetes mellitus: results of an international and unified approach. Issue 12 (20th March 2020) - Nano, J.; Carinci, F.; Okunade, O.; Whittaker, S.; Walbaum, M.; Barnard‐Kelly, K.; Barthelmes, D.; Benson, T.; Calderon‐Margalit, R.; Dennaoui, J.; Fraser, S.; Haig, R.; et al.
Abstract: Aims: To select a core list of standard outcomes for diabetes to be routinely applied internationally, including patient‐reported outcomes. Methods: We conducted a structured systematic review of outcome measures, focusing on adults with either type 1 or type 2 diabetes. This process was followed by a consensus‐driven modified Delphi panel, including a multidisciplinary group of academics, health professionals and people with diabetes. External feedback to validate the set of outcome measures was sought from people with diabetes and health professionals. Results: The panel identified an essential set of clinical outcomes related to diabetes control, acute events, chronic complications, health service utilisation, and survival that can be measured using routine administrative data and/or clinical records. Three instruments were recommended for annual measurement of patient‐reported outcome measures: the WHO Well‐Being Index for psychological well‐being; the depression module of the Patient Health Questionnaire for depression; and the Problem Areas in Diabetes scale for diabetes distress. A range of factors related to demographic, diagnostic profile, lifestyle, social support and treatment of diabetes were also identified for case‐mix adjustment. Conclusions: We recommend the standard set identified in this study for use in routine practice to monitor, benchmark and improve diabetes care. The inclusion of patient‐reported outcomes enables people living with diabetes to report directly on their condition in a structured way. What's new?: Standardized monitoring of diabetes care can improve quality through routine audit and benchmarking. Inconsistencies between measures adopted in different countries hamper this process and undermine international comparisons. This study was the first multinational effort to recommend a standard list of outcomes that matter most to people with diabetes, and that can be used in routine clinical practice to monitor, benchmark and improve diabetes care. The essential outcomes relate to diabetes control, acute events, chronic complications, health service utilisation and survival, measured using routine administrative data and/or clinical records. Three instruments were recommended for annual measurement of patient‐reported outcome measures (PROMs): the WHO Well‐Being Index for psychological well‐being; the depression module of the Patient Health Questionnaire for depression; and the Problem Areas in Diabetes scale for diabetes distress.